Parametric study and improvement in fuel properties of pre-blended methyl esters from crude palm and rubber seed oil - Bokhari, A. (Trans Tech Publications Ltd, 2014)
Environmental emissions concerns and the precautions of energy supply have motivated curiosity in the growth of alternatives for fossil based energy carriers and chemicals. Biodiesel as an alternative fuel has a potential to overcome energy crisis and reduce exhaust emissions to environment. Unutilized Rubber seed oil (RSO) alkyl esters have a huge potential to avoid food scarcity issue with contributing to energy sector. Current research contributes to produce biodiesel from the crude blends of palm oil and RSO. Parameters that effect base transesterification were extensively studied and methyl esters were characterized according to international biodiesel standards. The low-temperature flow properties and oxidation stability of the produced methyl esters were enhanced by blending with Fossil Diesel (FD) fuel. Â© 2014 Trans Tech Publications, Switzerland.